Development and usability of functional activities specific training (FAST) table for stroke rehabilitation: mixed method design - Ayesha Afridi; Malik, Arshad Nawaz; Rathore, Farooq Azam (Journal of the Pakistan Medical Association, 2026)
Objective: To explore the current practices and trends of task-oriented training, to identify and validate functional tasks pool, and to develop the functional activities specific training table. Method: The two-staged, mixed-method study was conducted at Pakistan Railway General Hospital, Rawalpindi, Pakistan, from September 15, 2022, to February 20, 2023. Semi-structured interviews with thematic analysis were conducted in the first phase of stage I that comprised physiotherapists from different cities to assess trends regarding task-oriented training. In the second phase, functional tasks pool was identified from literature review and categorised into four key domains. Content validity index was done for the identification of functional tasks pool by physiotherapy experts, resulting in a list of functional tasks to be incorporated in the functional activities specific training table. A table prototype was developed, and usability assessment was done with the system usability scale in stage II by patients and physiotherapists. The qualitative phase included 22 physiotherapists. For content validity, 20 experts were invited, of whom 17 responded. Usability testing involved 20 physiotherapists and 20 patients. Data was analysed using Atlas.ti and Microsoft excel. Results: In stage I, there were 22 physiotherapists with mean age 35.09±2.81 years and mean clinical experience 5.45±0.59 years. Six interconnected themes were identified regarding current practices, while literature review led to a functional tasks pool with 200 activities that were categorised into upper extremity, lower extremity, balance, and cognition-based activities. Content validity index resulted in 100 activities suitable for functional activities specific training table. In stage II, the prototype design’s usability was rated by 20 patients with a mean score of 81.25±16.5, and by 20 physiotherapy experts with a mean score of 81.37 ± 11.77. Conclusion: Based on current practices and perception of Pakistani physiotherapists, a therapeutic functional activities specific training table was developed with 100 task-oriented training-based activities for stroke rehabilitation. It showed strong usability scores by both patients and therapists. Key Words: Functional activities, Mixed method, Rehabilitation tools, Task-oriented training, Usability testing.